Urinary transferrin as an early biomarker of diabetic nephropathy - Terzić, Brankica; Stanojević, Ivan; Radojičić, Zoran; Resan, Mirko; Petrović, Dejan; Maksić, Djoko; Djekić, Jelena; Ristić, Petar; Petrović, Milica; Mijušković, Mirjana (Vojnosanitetski pregled, 2021)
Background/Aim. Diabetic nephropathy is one of the leading cause of chronic kidney disease and end-stage renal disease. It occurs in 20%–40% of patients with diabetes mellitus and microalbuminuria is still considered as the first sign of diabetic nephropathy. Low sensitivity and specificity of microalbuminuria lead to more sensitive biomarkers that may be used to detect diabetic nephropathy at an earlier stage with a higher accuracy. This study was carried out to determine whether urinary transferrin can serve as an indicator of diabetic nephropathy. Methods. Our study included 80 type 2 diabetic patients who were classified into two groups: group 1 – normoalbuminuric patients (albumin excretion up to 30 mg/d); group 2 – microalbuminuric patients (albumin excretion from 30–300 mg/d), and 10 healthy controls.  All patients were older than 18, having the diabetic disease more than one year, glomerular filtration rate more than 60 mL/min/1.73 m2. Serum creatinine, glycosylated hemoglobin (HbA1c), and concentration of transferrin in the 24 h urine samples as well as in spot urine were measured using a highly sensitive one-step sandwich enzyme immunoassay kit. Results. Urinary transferrin was significantly higher in the microalbuminuric patients than in the normoalbuminuric ones and healthy control subjects. When comparing these goups according to the urinary transferrin concentration, we found a statistically significant positive correlation r = 0.584 (p < 0.001). There was no correlation between level of urinary transferrin and glycoregulation, and no correlation was found between transferrin and duration of diabetes. Conclusions. The results from this study provide the evidence that the urinary transferrin levels could be used as an early marker of diabetic nephropathy.
Keywords: diabetes mellitus; diabetic nephropathies; albuminuria; biomarkers; transferrin.